1999
DOI: 10.1007/s001340050915
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous pyelonephritis related to specific gas-forming Escherichia coli without diabetes mellitus

Abstract: A 60-year-old-man without a history of diabetes mellitus, or invasive manipulation or obstruction of the urinary tract was admitted for septic shock. Type I emphysematous pyelonephritis was clear in this case: gas within the renal parenchyma extending into the subcapsular region and the perirenal space was present on spiral computerised tomography (CT). Surgical nephrectomy was performed because biochemistry, urography and CT identified a damaged non-functioning left kidney. The outcome was favourable. All uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This may explain how emphysematous urinary tract infections develop in the absence of hyperglycemia with subsequent glucosuria. 4,11 In humans, periodontal disease and immunosuppression have also been reported as predisposing factors. 6,12 Traditional surgery including ureteronephrectomy was the recommended therapeutic intervention in human medicine until recently, with the increasing utilization of interventional techniques such as percutaneous catheters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may explain how emphysematous urinary tract infections develop in the absence of hyperglycemia with subsequent glucosuria. 4,11 In humans, periodontal disease and immunosuppression have also been reported as predisposing factors. 6,12 Traditional surgery including ureteronephrectomy was the recommended therapeutic intervention in human medicine until recently, with the increasing utilization of interventional techniques such as percutaneous catheters.…”
Section: Discussionmentioning
confidence: 99%
“…A shift occurred in the 1980s with the standard of care being minimally invasive techniques in combination with medical management for EPN and other causes of ureteral obstruction. [4][5][6]8,11 Percutaneous drainage (eg, drainage via catheters or stents placed with computed tomographic guidance) is recommended for patients with localized areas of gas who still possess functioning renal tissue. 6 Complication rates and failure following minimally invasive techniques alone does increase with increasing severity of EPN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 2 However, certain strains of E coli are able to produce large amounts of nitrogen, carbon dioxide, and hydrogen in vitro, 3 4 and have been shown to cause gas accumulation in vivo-for example, in emphysematous pyelonephritis. 5 Serial thoracic CT scans showed that the intramyocardial air collections decreased in size during antibiotic treatment. Unfortunately, the patient died during an episode of ventricular fibrillation.…”
Section: Case Reportmentioning
confidence: 99%